Virulensi Fusarium oxysporum f.sp. zingiberi Isolat Boyolali dan Temanggung setelah Disimpan Enam Tahun dalam Tanah Steril - Andry Slamet Riyadi; Loekas Soesanto; Kustantinah Kustantinah (Jurnal Perlindungan Tanaman Indonesia, 2008)
This research aimed to study growth ability and virulence of several Fusarium oxysporum f.sp. zingiberi isolates originated from Boyolali and Temanggung after being preserved for six years in sterile soils media. Completely Randomized Design was used with 12 treatments and 3 replications. F. oxysporum f.sp. zingiberi originated from Temanggung consisted of 7 isolates, i.e., TKO1, TKO3, TKO4, TKO6, TKO7, TPO1, TPO5; and from Boyolali consisted of 4 isolates, i.e., BAO2, BAO7, BAC, and BAP. Variables observed were growth on PDA, colony color, colony diameter, macroconidia and microconidia, mycelial dry weight, incubation period, attack area, and difference of fresh weight of rhizome. The result showed that all isolates of F. oxysporum f.sp. zingiberi both from Temanggung and Boyolali were able to grow well on PDA and fully covered the Petridish at 4.75–7.5 days. The most virulent isolate was TKO6 from Temanggung showing the fastest incubation period of 5 days after inoculation and the highest attack area of 420 mm2 or increase for 107.6%.